PROFIL HORMON TESTOSTERON RUSA TIMOR (Cervus timorensis) JANTAN DALAM SATU SIKLUS RANGGAH (Testosterone Hormone Profile in One Antler Cycle of Timor Deer (Cervus timorensis) stag) - R. Handarini; W. M. Nalley (Media Konservasi, 2008)
The growth and replacement of stags antler on temperate species is physiologically linked to the seasonal rhythms of reproductive hormones. The objective of this research was to determine the pattern of testosterone hormone secretion in timor stags during one annual antler cycle which could be used to determine the active reproductive period of the stag. This research was conducted for 18 months in four adult timor stags (4 – 6 years of age). Blood samples were collected at three weeks intervals for analysis of testosterone hormone using the radioimmunoassay (RIA) method during one antler cycle (i.e. velvet, hard antler and casting stage). Results of this research showed significant difference (P